E-commerce and deliberate internationalization strategies - Pinto, Ana Filipa Amorim (2019)
Proposal: In the current international context, where there are more and more online consumers, it must be borne in mind that internet sales are in some way associated with exports. Technological developments have made the study of e-commerce in the international environment imperial because this type of commerce has enabled companies to conduct international transactions, reduce their transaction costs and access information more quickly. The main objective of this study is to define the factors that contribute to the use of this tool and its importance in the export strategy of companies. Design / Methodology / Approach: An empirical exploratory work was developed and five cases of Portuguese SMEs, representative of the national business fabric, were analyzed. Results: It has been observed that companies tend to recognize the advantages inherent in using e-commerce and have them as the basis of their decisions to start an online presence. It was assumed that reducing transaction costs and improving relationships (with customers, suppliers, partners and employees), as well as access to information, were the main reasons for companies to sell online. However, the first two turned out to be truly relevant. Limitations / Implications: The main limitations relate to the size of the sample and the fact that the research was conducted solely from the perspective of the companies, and only three propositions were tested. Originality / Value: While one might think that there is a prime strategic purpose to choosing online channel selling as a form of active internationalization, the truth is that the main motivation for starting online selling is primarily just as a more economical alternative distribution channel for Portuguese SMEs.